ASXL2 mutations are frequently found in pediatric AML patients with t(8;21)/ RUNX1‐RUNX1T1 and associated with a better prognosis. Issue 5 (14th February 2017) - Yamato, Genki; Shiba, Norio; Yoshida, Kenichi; Shiraishi, Yuichi; Hara, Yusuke; Ohki, Kentaro; Okubo, Jun; Okuno, Haruna; Chiba, Kenichi; Tanaka, Hiroko; Kinoshita, Akitoshi; Moritake, Hiroshi; et al.
Abstract: ASXL2 is an epigenetic regulator involved in polycomb repressive complex regulation or recruitment. Clinical features of pediatric acute myeloid leukemia (AML) patients with ASXL2 mutations remain unclear. Thus, we investigated frequencies of ASXL1 and ASXL2 mutations, clinical features of patients with these mutations, correlations of these mutations with other genetic alterations including BCOR/BCORL1 and cohesin complex component genes, and prognostic impact of these mutations in 369 pediatric patients with de novo AML (0–17 years). We identified 9 (2.4%) ASXL1 and 17 (4.6%) ASXL2 mutations in 25 patients. These mutations were more common in patients with t(8;21)(q22;q22)/ RUNX1‐RUNX1T1 ( ASXL1, 6/9, 67%, P  = 0.02; ASXL2, 10/17, 59%, P  = 0.01). Among these 25 patients, 4 (27%) of 15 patients with t(8;21) and 6 (60%) of 10 patients without t(8;21) relapsed. However, most patients with relapse were rescued using stem cell transplantation irrespective of t(8;21). The overall survival (OS) and event‐free survival (EFS) rates showed no differences among pediatric AML patients with t(8;21) and ASXL1 or ASXL2 mutations and ASXL wild‐type (5‐year OS, 75% vs. 100% vs. 91% and 5‐year EFS, 67% vs. 80% vs. 67%). In 106 patients with t(8;21) AML, the coexistence of mutations in tyrosine kinase pathways and chromatin modifiers and/or cohesin complex component genes had no effect on prognosis. These results suggest that ASXL1 and ASXL2 mutations play key roles as cooperating mutations that induce leukemogenesis, particularly in pediatric AML patients with t(8;21), and these mutations might be associated with a better prognosis than that reported previously.